If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(x+2)+2x=8(x-2)+8
We move all terms to the left:
6(x+2)+2x-(8(x-2)+8)=0
We add all the numbers together, and all the variables
2x+6(x+2)-(8(x-2)+8)=0
We multiply parentheses
2x+6x-(8(x-2)+8)+12=0
We calculate terms in parentheses: -(8(x-2)+8), so:We add all the numbers together, and all the variables
8(x-2)+8
We multiply parentheses
8x-16+8
We add all the numbers together, and all the variables
8x-8
Back to the equation:
-(8x-8)
8x-(8x-8)+12=0
We get rid of parentheses
8x-8x+8+12=0
We add all the numbers together, and all the variables
20!=0
There is no solution for this equation
| -11=-11u | | -5(-7m-8)=9+4m | | x+49=-29 | | (6x+58)+(9x−1)=87 | | 8n+6=11n-30 | | 9+25=5+x | | -8(x+4)+39=16-9x | | 2x+10.5x=-10 | | 2x/3=12/15 | | -13=2b-b=10 | | 12-3x=-5x | | 3.5x=2/5 | | N-7=-(n-5) | | -237=-3(11+5x)-2x | | 0.3x+1.8=0.4(x+5)=0.2 | | -9x-1=-8x+15 | | 2x⁄3=12/15 | | 2x+10.5x=25 | | 2/1 r−3=3(4−2/3r) | | y+11=42 | | 3.2n+n=5 | | -387=-9(-5x+3) | | -5+6m=7 | | 12)-2=(n-8) | | -3(4a+4)=-108 | | 8(x-8)+2x=3(x-8)+11x | | m-30=35 | | 6x-8x=-2(x+2)+7 | | 3x/18=6 | | 40+8x=-8(x+5) | | 5x=8=3x-3 | | c+-5=-9 |